TRIBOLOGICAL BEHAVIOR OF PTFE COMPOSITE MATERIAL FOR JOURNAL BEARING - Mr. P. D. Pansare; Prof. D. S. Bajaj; Prof. V. S. Aher (International Journal of Innovations in Engineering Research and Technology, 2021)
Polytetrafluroethylene (PTFE) is an important engineering material. When rubbed or slide against a hard surface, PTFE exhibits a low coefficient of friction but a high rate of wear. So to enhance the wear rate of PTFE, different fillers are added. In this study, the effect of load and sliding velocity on friction and wear of materials made of PTFE and PTFE composites with filler materials such as 25% carbon, 35% carbon, 40% bronze, 15% glass fiber, 15% glass fiber + 5% MoS2 have studied. The experimental work has performed on pin-on-disc friction and wear test rig and analyzed with the help of Design Expert software. The results of experiments are presented in tables and graphs which shows that the addition of carbon, bronze, glass filler to the pure PTFE decreases wear rate significantly and there is slight increase in coefficient of friction.